Effect of Cassava Fermentation on Reducing Sugar and Sucrose Levels: A Preliminary Study of Healthy Snack Development - Debora Helsius SB; Inayah Inayah; Desty Ervira Puspaningtyas; Puspita Mardika Sari; Nanda Herdiyanti Kusuma (Research Synergy Foundation, 2023)
One of the causes of obesity in Indonesia is poor consumption patterns, especially those high in sugars such as reducing sugar and sucrose. Indonesia's food diversity has the potential to be developed as a solution to obesity problems. The fermentation process is able to change the nutritional value composition, especially in reducing sugar and sucrose as healthy food. This research functioned as a preliminary study in the development of healthy snacks, especially for obesity, in terms of the presence and amount of reducing sugars and sucrose in cassava tape, gathot, and growol. This was carried out in two stages. The first stage was a qualitative analysis to examine the presence of carbohydrates through the Molisch test, Benedict's test, and Iodine test. Reducing sugar and sucrose levels were determined through quantitative testing using Nelson Somogyi with three replications for each sample. The research was conducted for seven months (January-July 2019) located at Universitas Respati Yogyakarta and Chem-mix Pratama Laboratory. Differences in reducing sugar and sucrose levels were tested with One Way ANOVA and continued with the Tukey test. Cassava, cassava tape, gathot, and growol contain monosaccharides and polysaccharides. Growol's reducing sugar content was only 0.32% (the lowest compared to other products, p<0.001) in line with the qualitative test results on Benedict's test. Sucrose levels from lowest to highest were gathot (0.78%), cassava tape (1.47%), growol (2.36%), and cassava (4.77%) (p<0.001). Growol has the potential to be developed as a healthy snack for obesity in terms of reducing sugar and sucrose levels.